Gene polymorphism and plasma levels of miR-155 in diabetic retinopathy. Issue 12 (December 2019) - Polina, E R; Oliveira, F M; Sbruzzi, R C; Crispim, D; Canani, L H; Santos, K G
Abstract : Circulating microRNA-155 (miR-155) is associated with type 2 diabetes mellitus (T2DM) and the rs767649 polymorphism in the pre-MIR155 gene is associated with miR-155 expression. However, their relationship with diabetic retinopathy (DR) is still unknown. Therefore, the aim of this case-control study was to test the hypothesis that the rs767649 polymorphism in the pre-MIR155 gene is associated with DR in South Brazilians with T2DM. We also evaluated the association of plasma levels of miR-155 with DR and the rs767649 polymorphism in a subgroup of subjects. The rs767649 polymorphism was genotyped in 139 blood donors and 546 T2DM patients (244 had no DR, 161 had non-proliferative DR and 141 had proliferative DR). miR-155 expression was quantified in 20 blood donors and 60 T2DM patients (20 from each group). Among T2DM patients, the carriership of the A allele and the A allele were more frequent in subjects with DR than in those without it ( P  < 0.05), and the A allele was independently associated with an increased risk of DR (adjusted OR = 2.12, 95% CI = 1.12–4.01). The plasma levels of miR-155 were lower in T2DM patients than in blood donors ( P  < 0.001). However, the miR-155 levels did not differ according to the presence and severity of DR or according to rs767649 genotypes among T2DM patients. These findings support that the rs767649 polymorphism in the pre-MIR155 gene is associated with DR in T2DM and that the miR-155 plasma levels might be associated with T2DM. Additional studies are needed to further investigate their clinical significance in DR and T2DM.